Ideological functions of the Tengriism - Feldman, Vladimir R. (The New Research of Tuva, 2011)
A report of the participant of the 3rd International Science and Practice Conference "Tengriism and epic heritage of Eurasian people: origins and modernity” (July 1-3, 2011).
Keywords: Tengriism; Central Asia; civilization; power; ideology; social organization; self organization; spiritual culture